Comparison of R&D Expenditures in Selected Countries; Poroẃnanie nakładoẃ na działalnosćB́+R w roźṅych krajach - Marlena Piekut (Comparative Economic Research. Central and Eastern Europe, 2013)
This paper analyzes the level of innovation expenditures and R&D fund sources in selected countries of the world in the period of 2000 - 2010. The issues presented indicate significant differences between the discussed countries with respect to the factors analyzed. The European countries at the top were apparently Finland, Denmark and Sweden. High R&D expenditures, with a significant share in business enterprise sector, and a large number of patent applications reflected on the strong economic growth in these countries. The level of R&D investments in these countries was sometimes greater than in the USA or Japan. Dynamic growth in both R&D and patent activity has also been observed in South Korea. Special attention has been paid in this paper to the new European Union members - Central Eastern European Countries. Among this group of countries Slovenia definitely had the highest position, where R&D expenditures were the largest and the structure of R&D funds by source reflected a businessdominance type. Estonia, Czech Republic and Hungary were the countries 'catching up' - where growth in R&D expenditures has been observed as well as better dynamics of growth and higher patent activity. Romania, Bulgaria, Lithuania, Poland, Slovakia and Latvia had relatively disadvantageous situations in respect of R&D development and the innovative activity of business enterprises. – – Celem artykułu była analiza poziomu i struktury finansowania działalnosći badawczo-rozwojowej w wybranych krajach oraz skonfrontowanie tych wskazńikoẃ z aktywnosćia patentowa i innowacyjnosćia przedsiebiorstw. Okres badawczy stanowiły lata 2000-2010. Do zobrazowania podobienśtw i roźṅic w nakładach na działalnosćB́+R pomiedzy analizowanymi krajami zastosowano analize skupienḿetoda Warda. Poziom finansowania działalnosći B+R polaryzuje Europe. Kraje Europy Poĺnocnej i Europy Zachodniej charakteryzuja wieksze nakłady na B+R i wiekszy udział przedsiebiorcoẃ w finansowaniu tych działan\'. Kraje bedace w czołoẃce to Finlandia, Dania i Szwecja. Korzystne wyniki osiagaja tezṄiemcy i Austriacy. Rumunia, Bułgaria, Litwa, Polska, Słowacja, Łotwa i Wegry to kraje z relatywnie niekorzystna sytuacja w zakresie rozwoju działalnosći B+R i innowacyjnosći podmiotoẃ gospodarczych. Sposŕod́ krajoẃ wschodniego regionu zdecydowanie wyzṡze pozycje w tym konteksćie zajmuje Słowenia. Realizacja celoẃ polityki UE w wielu krajach jest jeszcze odległa. Dalsze analizy powinny koncentrowacśie na znalezieniu optymalnego poziomu inwestycji w B + R w roźṅych sektorach.
Keywords: 330